Aplikasi Pengacakan Soal Ujian Online - M.Syaifuddin Zuhri; Agung Riyantomo (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2023)
The exam process, which is still manual or uses paper and writing instruments, has many weaknesses, including the duplication and distribution of question papers that require money and are not guaranteed to be safe, the use of unlimited answer sheet paper, the inaccuracy in the time of execution and collection of exam answers, examination of answer sheets. which takes quite a long time and cheating will also occur when working on exam questions because students can share answers to other students because the exam questions given are the same. This study aims to build applications for randomizing online exam questions that can facilitate the process of scoring or evaluating exam results and can avoid cheating that occurs when working on exam questions. The application of randomization of online exam questions can be used for the process of randomizing online exam questions so that online exams can avoid cheating and facilitate the assessment results or exam scores. The total score of the online exam scores is calculated using the formula for the number of correct / number of questions * 100.